Long Tail Hardware: Turning Device Concepts Into Viable Low Volume Products - Hodges, Steve; Chen, Nicholas (IEEE Pervasive Computing, 2019)
At a time when the technology industry is embracing powerful new algorithms and cloud computing, continued innovation in hardware is essential. In addition to the growing storage and computation requirements of data centers and edge computers, hardware devices provide the critical gateway through which our systems receive input and provide output. Whether it is intentional user interaction, continuous context sensing, situated information display, environmental monitoring, or industrial control, we are more dependent on interactive and embedded hardware products than ever. Indeed, as the Internet of Things grows, many predict a dramatic growth in both the number and type of such devices. A key factor in this growth is the ability of those working in hardware to develop innovative devices with new forms and functions. Hardware development can be split into two phases: first, a period of ideation, prototyping and design iteration leads to new device concepts; and then fruitful concepts transition beyond the basic prototype. The latter phase typically involves creating hundreds or thousands of copies of a prototype—either pre-production evaluation samples or a fully fledged low volume product. The hardware device research community and the industry it serves have developed many tools and techniques to aid in the ideation, prototyping, and design iteration phase mentioned above. However, based on our firsthand experience coupled with the observation of others, we frequently see a bottleneck in the subsequent phase—the transition from a working prototype to a viable product. The challenge of this bottleneck, its root causes, and the potential benefits of overcoming it are the subject of this column.